INFILTRASI NILAI EKOFEMINISME MELALUI PROGRAM BOGOR TANPA KANTONG PLASTIK PADA MASYARAKAT BANTARAN SUNGAI CILIWUNG DI KOTA BOGOR - Dwi Rini S. Firdaus; Intan Tri Kusumaningtias; Suryani I.P. Puwa (Media Bahasa, Sastra, dan Budaya Wahana, 2020)
This research aims to identify the influence of individual’s characteristics in East Bogor district and the effectiveness of the Bogor without Plastic Bags campaign to the community's concern about the environment. This study uses a descriptive quantitative approach to people who live on the banks of Ciliwung River at Eastern Bogor subdistrict. There are 100 respondents chosen by clustering and accidental sampling. The analysis uses multiple linear regression analyses, testing requirements of test normality, multicholinerity test and heteroskedastisity test. The results through T test shows that there is no influence between the individual characteristics (X1) towards the concerns about the environment (Y), except gender, especially women who have a partial influence on environmental concern. Meanwhile, the Bogor without plastic bags campaign (X2) significantly affects concerns about the environment (Y). The F test result indicates that variable (X1) and (X2) affect variable (Y) simultantly. The coefficient of determination (R2) is 47.8%, meaning that this study contributes 47,8% in giving solution to the problem about plastic bags in Bogor city. This study discusses the situation that Ciliwung River is facing, is related to the perspective of ecofeminism that nurturing nature is the same thing as nurturing women, women can do their role from home to control the production of plastic waste by not throwing waste into the river. Keywords: Bogor without Plastic Bags, Ecofeminism, Environmental                  Communication